(untitled) (International Journal of Innovative Technologies in Economy, 2022)
The main objective of this study is to examine the existence and nature of the relationship between the exchange rate and foreign exchange reserves. To avoid influencing foreign exchange market expectations, the intervention program should indicate in advance the nature, frequency, and size of the central bank’s foreign exchange transactions. Thus, in this sense, it is essential to determine the nature of the relationship between the exchange rate and the interventions made from and for the official foreign exchange reserve. Following the realization of this study, it was highlighted the conclusion that through the application of Johansen cointegration tests, between the pairs of variables - NEER and the interventions from/for the foreign exchange reserve; official exchange rate and interventions in/for the foreign exchange reserve - there is at least one cointegration relationship. That is, between the exchange rate and the interventions in/for the foreign exchange reserve, a long-term relationship is highlighted, which can facilitate the forecast.